2018
DOI: 10.1007/s10461-018-2350-8
|View full text |Cite
|
Sign up to set email alerts
|

Lower Neurocognitive Functioning Disrupts the Effective Use of Internet-Based Health Resources in HIV Disease: The Mediating Effects of General Health Literacy Capacity

Abstract: HIV-associated neurocognitive impairment is an independent predictor of low general health literacy, which can be associated with poor disease outcomes (e.g., viremia). Given the increasing frequency with which health behaviors occur in an online environment (e.g., health information seeking, provider interactions), there is a specific need to understand the predictors of electronic health (eHealth) literacy of persons living with HIV disease. In this study, 90 HIV+ persons completed the eHealth Literacy Scale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 51 publications
1
3
0
Order By: Relevance
“…These findings align with studies showing that the medio-temporal and prefrontal brain networks that support memory and executive functions are active during INS task performance (Dong et al, 2015;Small et al, 2009). A handful of studies now show that HIV-associated neurocognitive impairment is independently related to lower INS for both household (Woods et al, 2017) and health-related (Woods et al, 2016;Woods & Sullivan, 2019) tasks. Only one pilot study has specifically examined the neurocognitive aspects of online pharmacy skills.…”
Section: Introductionsupporting
confidence: 86%
See 1 more Smart Citation
“…These findings align with studies showing that the medio-temporal and prefrontal brain networks that support memory and executive functions are active during INS task performance (Dong et al, 2015;Small et al, 2009). A handful of studies now show that HIV-associated neurocognitive impairment is independently related to lower INS for both household (Woods et al, 2017) and health-related (Woods et al, 2016;Woods & Sullivan, 2019) tasks. Only one pilot study has specifically examined the neurocognitive aspects of online pharmacy skills.…”
Section: Introductionsupporting
confidence: 86%
“…For the average adult, these issues can make Internet navigation more cumbersome and challenging, but they can be especially difficult for individuals with neurocognitive disorders. Indeed, neurocognitive impairment is associated with higher rates of self-reported problems independently navigating technology (Nygård et al, 2012), including the Internet (Woods & Sullivan, 2019). In a recent systematic review, reported reliably and broadly medium-to-large effect sizes for the relationship between INS performance and a wide range of neurocognitive functions, most notably episodic learning and memory.…”
Section: Introductionmentioning
confidence: 99%
“…It is unlikely that the lack of significant findings were due to Type II error, as the current study sample of 217 participants was well-powered to detect small-to-medium effect sizes. These results were surprising, as other studies have demonstrated an association between neurocognition and electronic health literacy (e.g., Woods & Sullivan, 2019), as well as performance on naturalistic online search tasks . Other neurocognitive domains not assessed (e.g., spatial cognition, visual problem-solving) could still play an important role in information-seeking skills.…”
Section: Discussionmentioning
confidence: 60%
“…Poor health literacy is associated with adverse health outcomes: navigation difficulties within the health system, inaccurate or incomplete reports related to medical history, missed doctor appointments, inaccurate use of medications in terms of timing or dosage decreased rates of adherence to chronic illness regimens and increased risk of hospitalization (Baker et al, 1996 , 1998 , 2002 ; Williams, Baker, Honig, Lee, & Nowlan, 1998 ). Health literacy was also found to be associated with functioning in the digital domain, so that low health literacy (and related skills) are negatively related to the ability to understand (Woods & Sullivan, 2019 ; Zikmund-Fisher, Exe, & Witteman, 2014 ), evaluate online health information and trust in online health information (Diviani, van den Putte, Giani, & van Weert, 2015 ). Reviews (Berkman, Sheridan, Donahue, Halpern, & Crotty, 2011 ; Neter & Brainin, 2019 ) indicate consistent evidence on the association between health literacy and mortality, persisting after controlling for socioeconomic status, age, and race.…”
Section: Health Literacy Ehealth Literacy and Their Association With Health Outcomesmentioning
confidence: 99%